2021
DOI: 10.3390/rs13081556
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Topographic Changes and Land Subsidence Associated with the Mountain Excavation and City Construction on the Chinese Loess Plateau

Abstract: A mega project, Mountain Excavation and City Construction (MECC), was launched in the hilly and gully region of the Chinese Loess Plateau in 2012, in order to address the shortage of available land and create new flat land for urban construction. However, large-scale land creation and urban expansion significantly alters the local geological environment, leading to severe ground deformation. This study investigated the topographic changes, ground deformation, and their interactions due to the MECC project in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…For Regions D and E, some newly significant displacement areas were discovered during the period from December 2019 to March 2021, particularly in Region D. We can see from Figure 11c,d that the severe decorrelation signals occurred in the new displacement areas of Region D, indicating that the lands in these areas were created between December 2017 and December 2019. Besides, the displacement rate maps illustrate that non-uniform displacement exists in the MECC areas; this may be correlated with the thickness of the filling loess [4] and will be discussed in detail in Section 5.3. Compared with Figures 10 and 11, we found that most of MECC areas completed before 2005 were basically stable, and the main urban of Lanzhou was also stable.…”
Section: Spatial Distribution Of the Surface Displacement In Lanzhoumentioning
confidence: 95%
See 4 more Smart Citations
“…For Regions D and E, some newly significant displacement areas were discovered during the period from December 2019 to March 2021, particularly in Region D. We can see from Figure 11c,d that the severe decorrelation signals occurred in the new displacement areas of Region D, indicating that the lands in these areas were created between December 2017 and December 2019. Besides, the displacement rate maps illustrate that non-uniform displacement exists in the MECC areas; this may be correlated with the thickness of the filling loess [4] and will be discussed in detail in Section 5.3. Compared with Figures 10 and 11, we found that most of MECC areas completed before 2005 were basically stable, and the main urban of Lanzhou was also stable.…”
Section: Spatial Distribution Of the Surface Displacement In Lanzhoumentioning
confidence: 95%
“…The time-variable pseudo displacement signals can be generated in the case when the DEM errors are not exactly corrected [24]. However, a completed processing procedure for the DEM errors is not obtained in those previous studies [2,4,5,23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations